Effectiveness and safety of two phototherapy devices for the humanised management of neonatal jaundice - Adriana Montealegre; Nathalie Charpak; Adriana Parra; Claudia Devia; Isabel Coca; Ana María Bertolotto (Elsevier, 2020)
Introduction: Neonatal jaundice is common, especially in premature infants. Compliance treatment protocols with standard serum bilirubin curves force the clinician to separate the child from the mother after birth for phototherapy. The objective of this study is to evaluate the effectiveness and safety of two innovative devices for phototherapy including a LED light mesh: one sleeping bag and one blanket compared to conventional hospital or ambulatory phototherapy. Methods: Two randomised clinical trials were conducted: one with newborns >2000 g at birth in the Neonatal Care Unit and the other with premature infants followed-up in an outpatient Kangaroo Mother Care (KMC) programme. The gold standard for bilirubin measurement was serum bilirubin, and ambulatory controls were performed with the Bilicheck®. Parents and health personnel completed a questionnaire on comfort and perceptions. Results: In the study using the bag, a linear regression was performed for the decrease in bilirubin in mg/dL/h, controlling by early jaundice (<36 h) and the device type. The results were similar between the two devices. For the blanket trial in the KMC programme, the decrease in bilirubin levels with the new device was significantly greater. No differences in temperatures, duration of phototherapy, re-admission, mortality, or side effects for both trials were found. Parents and staff satisfaction with the two devices was identical for the two trials. Conclusion: These two small studies add a ''grain of sand'' to humanisation of newborn care, avoiding the mother-and-child separation for both the intra-hospital high-risk hyperbilirubinaemia, as well as for the lower-risk hyperbilirubinaemia in an outpatient clinic. Resumen: Introducción: La ictericia neonatal es frecuente en los prematuros. El tratamiento oportuno actual con curvas estándar para fototerapia lleva al clínico a separar el bebe de su madre después del nacimiento. Se busca evaluar la efectividad y seguridad de dos dispositivos innovadores para fototerapia compuestos por mallas de luz LED: una bolsa para dormir y una manta comparadas con fototerapia convencional intrahospitalaria o ambulatoria. Métodos: Se condujeron dos experimentos clínicos aleatorizados: uno con neonatos > 2000 g en una unidad de recién nacidos y otro con prematuros en un programa de seguimiento ambulatorio. El patrón de oro para la medición de bilirrubinas fue la bilirrubina sérica y los controles ambulatorios fueron hechos con el Bilicheck®. Padres y personal de salud respondieron una encuesta sobre comodidad con los dispositivos. Resultados: En el estudio de la bolsa se realizó regresión lineal para descenso de bilirrubinas en mg/dl/h, controlando por ictericia de aparición temprana (<36 h) y tipo de dispositivo. No se encontró diferencia significativa entre los dispositivos. Para el estudio en el seguimiento ambulatorio el descenso de bilirrubina con la manta fue significativamente mayor. En ambos estudios no se encontraron diferencias significativas en temperaturas, duración de fototerapia, readmisiones, mortalidad o efectos secundarios; tampoco en los cuestionarios para padres y equipo médico sobre comodidad con los dispositivos. Conclusiones: Estos dos pequeños estudios son un ''grano de arena'' para la humanización del cuidado neonatal, evitando la separación madre-hijo, tanto para el manejo de la hiperbilirrubinemia intrahospitalaria como para la hiperbilirrubinemia de bajo riesgo en el paciente ambulatorio.